THE CORRELATION BETWEEN STUDENTS’ INTRINSIC MOTIVATION AND STUDENTS’ LEARNING ACHIEVEMENT IN INTERPRETIVE READING AND ARGUMENTATIVE WRITING COURSE AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHA - Rini Maliha (PBI 15 UMY 073, 2015)
*73 Students’ intrinsic motivation is one of the factors that can influence students’ learning achievement in Interpretive Reading and Argumentative Writing Course. The aims of this study is to investigate students’ intrinsic motivation in Interpretive Reading and Argumentative Writing Course at EED UMY, students’ learning achievement in Interpretive Reading and Argumentative Writing Course, and the correlation between students’ intrinsic motivation and students’ learning achievement in Interpretive Reading and Argumentative Writing Course at EED UMY. Data were collected from 102 students of batch 2014. This research was conducted at English Education Department. The instrument of the study was questionnaire from Lepper, Iyengar and Corpus (2005) which had been modified. Document score from the lecturer of Interpretive Reading and Argumentative Writing Course was used to measure students’ learning achievement. The data was analyzed using descriptive statistic and descriptive correlation processed in SPSS 22.0. The Pearson Product Moment correlation coefficient was used to see the correlation between students’ intrinsic motivation and students’ learning achievement in Interpretive Reading and Argumentative Writing Course. The result showed that students’ intrinsic motivation in Interpretive Reading and Argumentative Writing Course at EED UMY was in the middle category (49.94), meanwhile students’ learning achievement in Interpretive Reading and Argumentative Writing Course at EED UMY was in good category (72.99). The findings showed that there was a positive correlation between students’ intrinsic motivation and students’ learning achievement but it was included in the category of very low correlation. Therefore, the alternative hypothesis (H1) was supported while the null hypothesis (H0) was rejected. Keyword. Students’ intrinsic motivation, Students’ learning achievement